Scalable Lithiophilic/Sodiophilic Porous Buffer Layer Fabrication Enables Uniform Nucleation and Growth for Lithium/Sodium Metal Batteries - Zhang, Shao‐Jian; You, Jin‐Hai; He, Zhiwei; Zhong, Jiajie; Zhang, Peng‐Fang; Yin, Zu‐Wei; Pan, Feng; Ling, Min; Zhang, Bingkai; Lin, Zhan (Advanced functional materials, 2022)
Metallic lithium/sodium (Li/Na) is considered an attractive anode for future high‐energy‐density batteries. The root causes of preventing their applications come from uneven Li/Na nucleation and subsequent dendrite formation. Here, a cost‐efficient and scalable solid‐to‐solid transfer method for dense buffer layer construction on Li/Na anodes is proposed, and thin lithiophilic/sodiophilic buffer layers based on natural silk fibers derived carbon (SFC) and carbon nanotubes (CNTs) composites (denoted as SFC/CNTs) are adopted, which facilitate uniform Li/Na nucleation and dendrite‐free, lateral growth behavior upon recurring Li/Na plating/stripping processes. Lithiopilic/sodiophilic buffer layers enable long‐term cycling stability (>250 cycles) with high Coulombic efficiency (99.2% for Li and 98.8% for Na), low polarization, and flat voltage profiles. More importantly, the cycling performance of LiFePO4|Li pouch cells is largely enhanced with a lifespan of 390 cycles. Further, using ultra‐thin Li anodes (25 μm) also achieves stable LiNi1/3Mn1/3Co1/3O2|Li cells with 200 cycles under a low negative/positive ratio (1.67). Similar achievement is also realized in Na‐metal batteries with negligible capacity fading for over 600 cycles in Na3V2(PO4)3|Na cells, further demonstrating that SFC/CNT buffer layer is technically viable in practical batteries. This study provides a facile strategy for fabricating dense and uniform lithiophilic/sodiophilic buffer layers for low‐cost and scale‐up energy storage devices. Natural silk fiber derived N/S‐functionalized porous carbon flakes are elucidated to regular the lithium/sodium (Li/Na) growth patterns from vertical to lateral direction, and a novel solid‐to‐solid transfer method is applied for dense and uniform buffer layer fabrication. The modified Li/Na anodes reveal a high performance in Li‐based pouch cells (390 cycles), and negligible fading in Na‐based coin cells (600 cycles).